The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.psychres.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of normative performance on the UCSD Performance‐Based Skills Assessment‐Brief

Abstract: The UCSD Performance-Based Skills Assessment (UPSA) is a performance-based measure of functional capacity. The brief, two-domain (finance and communication ability) version of the assessment (UPSA-B) is now widely used in both clinical research and treatment trials. To date, research has not examined possible demographic-UPSA-B relationships within a non-psychiatric population. We aimed to produce and describe preliminary normative scores for the UPSA-B over a full range of ages and educational attainment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…However, in the present sample, only FC performance did not change over time, with MCCB scores showing a statistically significant practice effect in the context of very high correlations across the two assessments (Dunlop et al, 2017;Hodgins et al, 2018). The level of cognitive performance of our sample was approximately 0.5 SD on average less than a national normative sample used in the creation of the MCCB norms and performance on the functional capacity measure was 0.43 SD worse than the data published in a previous normative study of the UPSA (Vella et al, 2017).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, in the present sample, only FC performance did not change over time, with MCCB scores showing a statistically significant practice effect in the context of very high correlations across the two assessments (Dunlop et al, 2017;Hodgins et al, 2018). The level of cognitive performance of our sample was approximately 0.5 SD on average less than a national normative sample used in the creation of the MCCB norms and performance on the functional capacity measure was 0.43 SD worse than the data published in a previous normative study of the UPSA (Vella et al, 2017).…”
Section: Discussioncontrasting
confidence: 60%
“…The UPSA-B's two domains (Communication and Finance) result in a summary score ranging from 0 to 100. Average performance of healthy controls on the UPSA-B (Vella et al, 2017) was 83.7 with a standard deviation of 10.2.…”
Section: Performance-based Measures Of Functional Capacitymentioning
confidence: 99%
“…Consistent with previous findings (Garcia-Portilla et al, 2013;Mausbach et al, 2007;Patterson et al, 2001;Vella et al, 2017), the UPSA-2-PT results showed patients have a significant in functional capacity comparing to controls or their first-degree relatives, who were generally older participants.…”
Section: Ptsupporting
confidence: 91%
“…Neuropsychological tests that were significant at p<0.05 at the bivariate level were entered as predictors of UPSA-B and SSPA in forward selection stepwise regression models, along with associated psychiatric symptom severity variables and diagnostic category (major depression coded as 1; bipolar disorder coded as 2; schizophrenia-spectrum disorders coded as 3). Additionally, years of education was also included in the model given its demonstrated association with UPSA-B performance (Mausbach et al, 2010; Vella et al, 2017). There were significant demographic differences by diagnostic group in gender and racial/ethnic minority status ( p s<0.05); however, these were not included within the regression models given the use of standardized t-scores.…”
Section: Methodsmentioning
confidence: 99%